Pelatihan dan Sekolah Lapang Terpadu Kabupaten Bulukumba - Mardiana Ahmad; Suryani As'ad; Andi Alief Aminuddin; Rusnawati Rusnawati (STKIP Andi Matappa, 2021)
Taccorong Village in Ujung Bulu Subdistrict is one of the villages with the highest death toll in the Bulukumba Regency. There were 33 cases of neonatal deaths in 2015. In anticipation of this event, Training and integrated Field Schools activities through Clean and Healthy Lifestyle Counseling (PHBS), Balanced Nutrition Counseling, Early Breastfeeding Initiation Counseling (IMD), and Examination and Gymnastics of Pregnant Women. The approach method used in this devotional program is participatory education and training or educational and participatory approach both to health workers in Community Health Centers (Puskesmas) and Integrated Service Post (Posyandu) and for Village Health Worker of Integrated Service Post. This method positions the target audience as recipients of knowledge, understanding, and skills on how to change the lifestyle to be healthier, where the mother cadre group is involved in all activities ranging from planning, implementation, monitoring, and evaluation. In addition, participatory counseling is conducted by conducting learning activities. The activity was held for 2 (two) days, namely, on Saturday-Sunday, August 11-12-2018, with many workshop participants as many as 30 people. Workshop participants consisted of 3 health workers, Community Health Centers (Puskesmas), 12 cadres, and 15 citizens. The results of this devotion get participants have implemented the practice of Clean and Healthy Living Behavior, practiced the preparation of a balanced nutrition menu, especially at 1000 HPK, and has implemented early breastfeeding initiation (IMD)practices in the postpartum period. It is expected that this activity can be replicated throughout the village and can continue to support the improvement of public health